A Cost-Efficiency Analysis for Upper-Structure Construction Based on Value Engineering: A Case Study - Satrya Jaka Pratama; Retno Anggraini; Ming Narto Wijaya (CV. Creative Tugu Pena, 2026)
This study aims to analyze cost efficiency in the upper structure of multi-story buildings through a Value Engineering (VE) approach. The case study focuses on the construction project of the Joint Lecture Building 5 (GKB 5) at Muhammadiyah University Malang. The research focuses on identifying the upper structure components that dominate the costs and developing alternative materials and methods that still fulfill the structural function but are more cost-efficient. The VE process includes the stages of identifying work elements that require cost optimization, evaluating alternative solutions, and selecting the best alternative based on technical and cost considerations. The results of the study show that optimizing the reinforcement of columns, beams, and slabs, as well as changing the formwork system from conventional to semi- system, can produce cost efficiencies of 8–14% without reducing the strength and safety of the structure. These findings confirm that VE can be a strategic tool for decision-making in high- rise building construction projects